Building Competitive Advantage through Human Capital and the Impact on Business Performance: Analysis at Individual and Organizational Level - Yuwanda, Tonny; Fadhlan, Abdi; Daud, Ilzar (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2023)
This research aims to determine sustainable strategies to improve business performance, focusing on creativity, innovative behavior, and psychological empowerment at the individual level, as well as digital leadership, competitive advantage, and business performance at the organizational level. This study employs a quantitative approach, where a questionnaire was distributed to 254 SMEs in West Sumatra, Indonesia, and the analytical technique used is path analysis using PLS-MGA. The results show that innovative behavior has a greater impact on business performance at the individual level, while digital leadership has a greater impact on business performance at the organizational level. Understanding these different impacts can help organizations understand how to apply the right practices to improve their business performance, either by enhancing innovative behavior at the individual level or by improving digital leadership at the organizational level.